The power of thank you : discover the joy of gratitude - Meyer, Joyce, 1943- (FaithWords, 2022)
"Adopt a lifestyle of thanksgiving and discover that no matter how messy life gets, God will make it good. Each moment that you're given is a precious gift from God. You can choose to have a thankful attitude and live each moment full of joy, simply because God is good. In The Power of Thank You, renowned Bible teacher and #1 New York Times bestselling author Joyce Meyer encourages us to take a look at ourselves and the importance of being thankful. Living life with a heart of gratitude for who God is and what He has done lifts your burdens and allows you to see everything in a different light. Regularly giving thanks to God not only helps you fully realize how He's working in your life, it gives you a new perspective-your mind is renewed, your attitude is improved, and you're filled with joy. Things will certainly happen to you that don't seem fair, and it's much easier to make excuses and feel sorry for yourself. Keep saying, "I trust You, God, and I believe You will work it all out for my good." If you find The Power of Thank You in every situation, truly believing that God is working everything out for your good, you will end up with the victory every single time"--